MARRIED COUPLES WITH DIFFERENT COMBINATIONS OF ATTACHMENT STYLES: DIFFERENCES IN THE PERCEPTION OF THE MARITAL QUALITY - Trifunović, Biljana; Šakotić-Kurbalija, Jelena; Strizović, Ivana (Primenjena psihologija, 2016)
To examine differences in the perception of marital quality among couples with various combinations of attachment styles, a total of 332 couples of diverse socioeconomic status, aged between 17 and 81 were examined. Administered scales were: the Dyadic Adjustment Scale (DAS: Spanier, 1976, 1989) for measuring marital quality and the Experiences in Close Relationships Scale − Short Form (ECR: Brennan, Clark, & Shaver, 1998; modification: Kamenov & Jelić, 2003) for identifying adult attachment styles. To assess the differences between couples with various combinations of attachment styles across the four factors of marital quality (dyadic consensus, dyadic satisfaction, affectional expression, and dyadic cohesion) one-way MANOVA was performed. Results indicate that the couples in which both partners are insecurely attached report worse adjustment in all examined factors of marital quality than couples in which either or both partners are securely attached. However, secure couples (in which both partners are securely attached) report significantly higher scores only on the Dyadic Consensus scale than mixed couples (in which only one partner is secure). No other differences are reported between these two groups.